2020
DOI: 10.1080/13669877.2020.1779785
|View full text |Cite
|
Sign up to set email alerts
|

The emotional engagement of climate experts is related to their climate change perceptions and coping strategies

Abstract: The emotional engagement of climate experts is related to their climate change perceptions and coping strategiesThe study aimed to reveal the role of emotions in Lithuanian climate experts' perceptions of climate change (i.e., their beliefs about the causes and risk perceptions of climate change) and fill the gap in scientific knowledge about the coping strategies that climate experts tend to employ in order to deal with climate-change-related emotions.To investigate climate experts' emotional reactions to cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 44 publications
(81 reference statements)
2
14
0
Order By: Relevance
“…These findings are largely congruent with the findings of Van der Linden [22] and Xie et al [23]. While the importance of affect in shaping risk perceptions was diminished in earlier research [57], more recent research largely endorses the idea that emotions and affect play a crucial role in forming climate change risk perceptions [22,23,31,[58][59][60][61][62][63][64]. Therefore, since once again the importance of emotions and affect in understanding risk perceptions of climate change is underscored, the need for future research focusing on how emotions can-and should-be addressed in climate change communications is paramount.…”
Section: Evaluation Of Ccrpm+supporting
confidence: 74%
“…These findings are largely congruent with the findings of Van der Linden [22] and Xie et al [23]. While the importance of affect in shaping risk perceptions was diminished in earlier research [57], more recent research largely endorses the idea that emotions and affect play a crucial role in forming climate change risk perceptions [22,23,31,[58][59][60][61][62][63][64]. Therefore, since once again the importance of emotions and affect in understanding risk perceptions of climate change is underscored, the need for future research focusing on how emotions can-and should-be addressed in climate change communications is paramount.…”
Section: Evaluation Of Ccrpm+supporting
confidence: 74%
“…Lazo et al (2000) found that laypeople showed more intense emotions than experts when perceiving climate change risks. Contrastingly, Jovarauskaite and Böhm (2020) found that experts tended to show more intense negative emotions (e.g., disappointment, sadness, guilt) to climate change impacts than laypeople. Experts experience diverse negative affective responses to perceived climate change risks including contempt, anger, worry, disappointment, guilt, and sadness (Jovarauskaite and Böhm, 2020).…”
Section: Lay People Vs Expertsmentioning
confidence: 61%
“…Contrastingly, Jovarauskaite and Böhm (2020) found that experts tended to show more intense negative emotions (e.g., disappointment, sadness, guilt) to climate change impacts than laypeople. Experts experience diverse negative affective responses to perceived climate change risks including contempt, anger, worry, disappointment, guilt, and sadness (Jovarauskaite and Böhm, 2020). Negative affective responses (e.g., fear) were common in laypeople, who, in some cases, tended to overestimate the potential risks (e.g., flooding) .…”
Section: Lay People Vs Expertsmentioning
confidence: 61%
See 2 more Smart Citations